2005
DOI: 10.1007/s00520-005-0884-6
|View full text |Cite
|
Sign up to set email alerts
|

Infections in a pediatric patient cohort with acute lymphoblastic leukemia during the entire course of treatment

Abstract: Most of the severe infections occurred during induction. Gram-positive bacteremia and Gram-negative bacteremia were almost equal. URIs were the commonest infections during the entire treatment and during maintenance. Specific viral infections represented a smaller percentage of the total (VZV was the commonest pathogen). Infectious complications represented a significant morbidity factor, but notably, mortality was negligible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 21 publications
3
50
1
1
Order By: Relevance
“…Gram positive organism Staphylococcus aureus also contributed in 2 (22.22%) occasions in this study. is is comparable to Katerina Katsimpardiet al 26 which also showed predominance of gram negative organism (Pseudomonas , K pneumonia and E coli). Chessell MJ and Leiper AD showed that the organism responsible for most infections were Pseudomonas aeroginosa followed by Staphylococcus aureus and E coli 24 , whereas Meir et al 27 found gram positive cocci followed by gram negative bacilli in most of the cases.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Gram positive organism Staphylococcus aureus also contributed in 2 (22.22%) occasions in this study. is is comparable to Katerina Katsimpardiet al 26 which also showed predominance of gram negative organism (Pseudomonas , K pneumonia and E coli). Chessell MJ and Leiper AD showed that the organism responsible for most infections were Pseudomonas aeroginosa followed by Staphylococcus aureus and E coli 24 , whereas Meir et al 27 found gram positive cocci followed by gram negative bacilli in most of the cases.…”
Section: Discussionsupporting
confidence: 82%
“…24 Cwiekliska M et al also found 40%-50% incidence of infection in their study. 25 In another previous study done by Katsimpardi K et al 26 showed that Pseudomonas aeroginosa, Klebsilla pneumonia and E coli were the organisms most commonly isolated. Meir et al 27 found 37% microbiologically documented infection where gram positive cocci followed by gram negative bacilli were isolated in most of the cases.…”
Section: Discussionmentioning
confidence: 92%
“…The delay in care seeking probably explains the higher complication rate seen in our study. Before the introduction of antiviral therapy, the mortality rate of VZI in children with cancer was reported to be 7%-10%, with rates reaching up to 55% in cases with visceral involvement [5,21,22]. The majority of our patients recovered from the disease and its complications, with an overall recovery rate of 97%.…”
Section: Discussionmentioning
confidence: 75%
“…Infection is the most frequent complication during chemotherapy for ALL [15]. Especially, remission induction therapy is often complicated by severe myelosuppression, and infection in this phase is sometimes causative of therapy-related death.…”
Section: Discussionmentioning
confidence: 99%